Z33 : (no. 0 - no. 7) = Z33 : (06/2002 - 10/2004) - Boelen, Jan; Derycke, Luc; Z33 (Hasselt : Z33, 2005)
Acconci, Vito ; Ant Farm ; Barba, Rosa ; Bastien, Pierre ; Beecroft, Vanessa ; Benglis, Lynda ; Benning, Sadie ; Birnbaum, Dara ; Brown, Don ; Byrne, James ; Canto, Siegfried ; Catrysse, Wim ; Charmatz, Boris ; Claerbout, David ; Clark, Larry ; De Clercq, Anouk ; Cool, Joris ; Corbijn, Anton ; Craighead, Alison ; Cunningham, Chris ; De Cupere, Peter ; Cuyvers, Wim ; Davis, Douglas ; Desbazeilles, Magali ; Devens, Paul ; Dijkstra, Rineke ; Doing, Karel ; Eerdekens, Fred ; Export, Valie ; Girardet, Christoph ; Godard, Jean-Luc ; Gontarski, Steven ; Gonzalez-Torres, Felix ; Grannan, Katy ; Granular Synthesis ; Grönlund, Tommi ; Harrison, Rachel ; Holloway, Evan ; Ikeda, Ryoji ; Jonas, Joan ; K., Alex ; Kelley, Mike ; Kempe, Anja ; Kieckens, Christian ; van Koolwijk, Bas ; Larcher, David ; Leckey, Mark ; Legrand, Jozef ; Lichty, Patrick ; López, Francisco ; McCarthy, Paul ; Migone, Christof ; Moorman, Charlotte ; Morawe, Volker ; Müller, Matthias ; Nisunen, Petteri ; Noland, Cady ; O'Reilly, Michael ; Paik, Nam June ; Periton, Simon ; Reiff, Tilman ; Reinke, Steve ; Rist, Pipilotti ; Robijns, Gert ; Sachs, Tom ; Sawyer, Mathew ; Schülke, Björn ; Shaw, Jeffrey ; Sierra, Santiago ; Sims, David ; St-Onge, Alexandre ; Svankmajer, Jan ; Swailow, Ricky ; Thomson, Jon ; Vanmechelen, Koen ; Vasulka, Steina & Woody ; Verschueren, Bob ; Wallace, Linda ; Wampler, Claude
Met teksten in het Nederlands en Engels.
boek